Impact of dark septate endophytes on salt stress alleviation of tomato plants - Gaber, Dalia A.; Berthelot, Charlotte; Blaudez, Damien; Kovács, Gábor M.; Franken, Philipp (Frontiers in Microbiology, 2023)
Fungal endophytes can improve plant tolerance to abiotic stress conditions. Dark septate endophytes (DSEs) belong to phylogenetically non-related groups of root colonizing fungi among the Ascomycota with high melanin-producing activities. They can be isolated from roots of more than 600 plant species in diverse ecosystems. Still the knowledge about their interaction with host plants and their contribution to stress alleviation is limited. The current work aimed to test the abilities of three DSEs (Periconia macrospinosa, Cadophora sp., Leptodontidium sp.) to alleviate moderate and high salt stress in tomato plants. By including an albino mutant, the role of melanin for the interaction with plants and salt stress alleviation could also be tested. P. macrospinosa and Cadophora sp. improved shoot and root growth six weeks after inoculation under moderate and high salt stress conditions. No matter how much salt stress was applied, macroelement (P, N, and C) contents were unaffected by DSE inoculation. . The four tested DSE strains successfully colonized the roots of tomato, but the colonization level was clearly reduced in the albino mutant of Leptodontidium sp.. Any difference in the effects on plant growth between the Leptodontidium sp. wild type strain and the albino mutant could, however, not be observed. These results show that particular DSEs are able to increase salt tolerance as they promote plant growth specifically under stress condition. Increased plant biomasses combined with stable nutrient contents resulted in higher P uptake in shoots of inoculated plants at moderate and high salt conditions and higher N uptake in the absence of salt stress in all inoculated plants, in P. macrospinosa -inoculated plants at moderate salt condition and in all inoculated plants except the albino mutants at high salt condition. In summary, melanin in DSEs seems to be important for the colonization process, but does not influence growth, nutrient uptake or salt tolerance of plants.